DIPG-15. THE ROLE OF THE G-PROTEIN-COUPLED RECEPTOR, GPR17 IN PAEDIATRIC DIFFUSE MIDLINE GLIOMA. Issue 2 (22nd June 2018) - Loveson, Katie; Lepinay, Eva; Robson, Samuel; Fillmore, Helen
Abstract: Pediatric diffuse midline glioma (pDMG), an incurable, aggressive childhood malignancy, arises in a region- and age-specific nature. The underlying pathophysiology suggests dysregulation of postnatal neurodevelopmental processes causing aborted cell differentiation. The cell of origin is as yet unclear, but recent data suggests an oligodendrocytic lineage. This is supported by the over-expression of transcription factors such as Olig1 & Olig2 in 80% of pDMG cases. Results from in-depth bioinformatics and principal component analysis (PCA) of genes involved in brain development and pDMG led us to explore GPR17. GPR17, an orphan G protein-coupled receptor has been identified in a number of physiological and pathological processes, such as oligodendrocyte differentiation, spinal cord injury and brain injury. Bioinformatic analyses of publicly available mRNA datasets (GSE26576), indicated a significant up-regulation of GPR17 in pDMG patients compared to normal brainstem (p = 0.0037) and normal brain (p < 0.0001). PCA analysis shows GPR17 clusters closely to Olig1 and Olig2. GPR17 expression was confirmed in cell lines (VUMC-DIPG-A and VUMC-DIPG-08) and FFPE tissue at protein level using Western blot, IHC and Flow Cytometry and mRNA level using RT-qPCR. To gain further understanding of the role of GPR17, we are currently using agonists, antagonists and shRNA to modulate GPR17 expression and activity in functional and mechanistic, signalling pathway studies. Preliminary results suggest that GPR17 may be associated with the biology of pDMG. Our study hopes to provide insight into the mechanism of action and to identify targets for this receptor as a potential approach for therapeutic intervention.